THE WORK OF JOHN FOWLES AND ITS PLACE IN POSTMODERN LITERATURE (Modern education and development, 2024)
In this article, John Fowles' work and his contribution to postmodern literature will be discussed briefly, as well as an analysis of the works. In addition, in this article, one can learn about his early literary efforts, creative ways and many manuscripts for publishing his works. He is also said to have honed his craft by studying and imitating the works of writers he admired, such as Flaubert, D.H. Lawrence, Defoe, and Hemingway.